2015
DOI: 10.1111/ppe.12199
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Hyperglycaemia and Risk of Prenatal and Postpartum Depressive Symptoms

Abstract: Background Glucose dysregulation in pregnancy may affect maternal depressive symptoms during the prenatal and postpartum periods via both physiologic and psychological pathways. Methods During mid-pregnancy, a combination of 50-gram 1-h non-fasting glucose challenge test (GCT) and 100-gram 3-h fasting oral glucose tolerance test (OGTT) was used to determine pregnancy glycemic status among women participating in Project Viva: normal glucose tolerance (NGT), isolated hyperglycemia (IHG), impaired glucose toler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
49
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 37 publications
7
49
3
Order By: Relevance
“…Our findings in a low-risk, diverse, US sample confirm those of a prior study from Iran [15]. Interestingly, other studies of the association between GDM and postpartum depression have been null, but these studies either assessed depression much later, at 6 months postpartum [12], or used a self-report of depression [13], unlike our study, which used a validated measure of depressive symptoms at 6 weeks postpartum.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our findings in a low-risk, diverse, US sample confirm those of a prior study from Iran [15]. Interestingly, other studies of the association between GDM and postpartum depression have been null, but these studies either assessed depression much later, at 6 months postpartum [12], or used a self-report of depression [13], unlike our study, which used a validated measure of depressive symptoms at 6 weeks postpartum.…”
Section: Discussionsupporting
confidence: 82%
“…There has also been conflicting evidence on whether GDM is a risk factor for postpartum depression. Of the studies that have prospectively examined this association, the findings have either been conflicting [1216] or have not distinguished between GDM and pre-existing type 2 diabetes [16]. …”
Section: Introductionmentioning
confidence: 99%
“…Overall, 48 publications were included in this review (Figure 1, Table 1, Table 2, Table 3, Supplementary Table 1). Of these, 30 described prospective observational studies[20,21,23,24,26,27,29-31,34,35,37,38,41,43-45,47-49,51,54,57,58,60-62,65-67], 15 described retrospective observational studies[22,25,28,32,39,40,42,46,50,53,55,56,59,63,64], and three described randomized controlled trials (RCTs)[33,36,52], two of which reported only baseline data[36,52]. Two publications described the same study, but reported different subgroup analyses[23,29].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 28 studies included only women with GDM[20,23,26-29,31,33,35-38,40,43-45,47-49,51-53,57,58,60,61,63,64], 14 included women with either GDM or pre-existing diabetes (although the type was not always reported)[22,25,39,41,42,46,50,54-56,59,62,65,66], one included women with either GDM or type 1 diabetes[34], one included only women with type 1 diabetes[67], one included only women with pre-existing diabetes (type not reported)[30] and three did not report the type of diabetes[21,24,32] (Tables 1-3, Supplementary Table 1). Sample sizes ranged from 36[65] to more than 32 million in a retrospective analysis of a nationwide hospital database[22] (Tables 1-3, Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation